الطريقة المثلى لحساب أنظمة التكييف المركزي واختيارها - عمران عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
في الآونة الأخيرة تزداد الحاجة لتأمين الشروط الحرارية المريحة لعمل الناس وإقامتهم ، ولهذا تم استخدام أنظمة مختلفة لتكييف الهواء في المكاتب والفنادق والمراكز التجارية وأماكن العمل وغيرها. في حالات كثيرة يكون استخدام أنظمة التكييف المركزي مع وحدات متممة (الفانكويل) أحد الطرق الأكثر فعالية وملاءمة وذلك حسب نوع الأبنية المراد تكييفها واستخداماتها ، لكن اختيار الوحدات المتممة بالطرق البسيطة المألوفة يعطي عادة وفي كثير من الحالات نتائج بعيدة عن المطلوب واقعياً. يقدم البحث طريقة لحساب أنظمة التكييف مع وحدات الملف والمروحة ( فانكويل)، ويصف عمليات معالجة الهواء على مخطط h-d ، واختيار الوحدات اللازمة لتحقيق الشروط الحرارية المريحة بأكبر فعالية وأقل كلفة في عمليات إنشاء واستثمار تلك الأنظمة . At present, there is a strong demand for comfortable heat conditions for people’s work and residence. For this reason, different air-conditioning systems are used in offices, hotels, trade centers, work places and others. In many cases, the usage of the central conditioning systems with complementary systems is one of the most effective and suitable ways depending on the type and usage of the buildings that will be conditioned, but the selection of the complementary units by simple familiar ways usually gives inaccurate results. The research presents a way to calculate the conditioning systems with complementary units, and it describes the air processing operations on the h-d diagram, and the selection of the necessary units for comfortable heat conditions in the construction and investment of these systems with less cost and more efficiency.